Synchrotron X‐Ray and Neutron Diffraction, Total Scattering, and Small‐Angle Scattering Techniques for Rechargeable Battery Research. Issue 8 (13th June 2018) - Ren, Yang; Zuo, Xiaobing
Abstract: Synchrotron X‐ray and neutron scientific facilities are the most advanced resources with a large variety of state‐of‐the‐art instrumentations and powerful tools for material research. X‐rays and neutrons interact with matter in different ways and offer complementary views of materials at various levels. Here, the techniques and applications of synchrotron X‐ray and neutron diffraction, total scattering, and small‐angle scattering for rechargeable battery research are discussed. They all belong to the elastic scattering category and provide structure information on different length scales. The diffraction method is generally used to determine the phase and precise atomistic information of crystalline materials, while the total scattering coupled with pair‐distribution function analysis can probe local atomic structure of materials, independent of whether they are well crystallized or in amorphous/liquid phases. The small‐angle scattering techniques provide material size and shape information on the nanometer scale. Advantages of synchrotron high‐energy X‐rays are also presented, and it is described to be particularly suited for pair‐distribution function studies. Attention is also paid to the technical perspectives and some experimental specifications for the best uses of these methods for battery material research. Abstract : Synchrotron X‐ray and neutron scattering techniques are widely used in rechargeable battery studies because they are nondestructive and can provide a broad spectrum of important structural information. A tutorial review on X‐ray and neutron diffraction, small‐angle scattering, total scattering, and pair distribution function analysis is given, and applications in battery material characterization and rechargeable battery mechanism studies are discussed.